2019
DOI: 10.1371/journal.pone.0209761
|View full text |Cite
|
Sign up to set email alerts
|

Can optical spectral transmission assess ultrasound-detected synovitis in hand osteoarthritis?

Abstract: Objective To determine whether optical spectral transmission (OST) can be used to assess synovitis in hand and wrist joints of patients with hand osteoarthritis (OA). Design Hand and wrist joints of 47 primary hand OA patients with at least one clinically inflamed hand or wrist joint were assessed for synovitis by OST and ultrasound (US). Associations between standardized OST and US synovitis were studied in linear mixed effects models, across all joint types together a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A total of 159 citations were identified for screening with 32 articles included for final analysis. Thirty articles evaluated US features of hand OA [ 24 , 25 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] and two assessed US OA features in the foot [ 65 , 66 ]. Twenty-seven hand OA studies assessed the proximal and distal interphalangeal joints [ 24 , 25 , 37 , 38 , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [59] , [60] , [61] , [62] , [63] , [64] ], 22 studies assessed the metacarpophalangeal and carpometacarpal joints [ 24 , 25 , [38] , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 159 citations were identified for screening with 32 articles included for final analysis. Thirty articles evaluated US features of hand OA [ 24 , 25 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] and two assessed US OA features in the foot [ 65 , 66 ]. Twenty-seven hand OA studies assessed the proximal and distal interphalangeal joints [ 24 , 25 , 37 , 38 , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [59] , [60] , [61] , [62] , [63] , [64] ], 22 studies assessed the metacarpophalangeal and carpometacarpal joints [ 24 , 25 , [38] , …”
Section: Resultsmentioning
confidence: 99%
“…The following inflammatory US features were investigated by the included studies: synovitis, synovial hypertrophy, joint effusion, tenosynovitis, and power Doppler (PD) signal. PD signal was the most reported US feature across all studies (n ​= ​24) [ 24 , [37] , [38] , [39] , [40] , [41] , 44 , [46] , [47] , [48] , [49] , [50] , [51] , [53] , [54] , [55] , 57 , 59 , 60 , [62] , [63] , [64] , [65] , [66] ]. There were also inconsistencies between the different entities of synovial pathology, making comparison between studies difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a Dutch study found moderate results with MRI as reference, while a Danish study concluded that the sensitivity of OST was not superior to clinical examination (195,196). The diagnostic performance of OST has also been investigated in hand OA, with fair performance in the PIP joints and poor performance in the DIP joints (197).…”
Section: Other Optical Imaging Modalitiesmentioning
confidence: 99%
“…The Handscan is an optical imaging device, designed for the visualization of hemodynamics related to joint inflammation by optical spectral transmission imaging of hands and wrists before, during and after venous occlusion at the lower arm. [11] It is a safe and fast measurement, which takes only 2 min [12]. By using this technique, the Handscan is supposed to be an objective measurement tool of inflammation.…”
Section: Introductionmentioning
confidence: 99%